2022
DOI: 10.1117/1.jmi.9.5.054504
|View full text |Cite
|
Sign up to set email alerts
|

Pre-deployment assessment of an AI model to assist radiologists in chest X-ray detection and identification of lead-less implanted electronic devices for pre-MRI safety screening: realized implementation needs and proposed operational solutions

Abstract: Purpose: Chest X-ray (CXR) use in pre-MRI safety screening, such as for lead-less implanted electronic device (LLIED) recognition, is common. To assist CXR interpretation, we "predeployed" an artificial intelligence (AI) model to assess (1) accuracies in LLIED-type (and consequently safety-level) identification, (2) safety implications of LLIED nondetections or misidentifications, (3) infrastructural or workflow requirements, and (4) demands related to model adaptation to real-world conditions.Approach: A two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…In this project, we showed that by using a common standards-based architecture and workflow the ability to deploy algorithms, whether vendor-based (commercial products or prototypes) or locally developed [7], can carry significant advantages. This approach enables support of complex operational requirements and allows both types of solutions to coexist in the same environment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this project, we showed that by using a common standards-based architecture and workflow the ability to deploy algorithms, whether vendor-based (commercial products or prototypes) or locally developed [7], can carry significant advantages. This approach enables support of complex operational requirements and allows both types of solutions to coexist in the same environment.…”
Section: Resultsmentioning
confidence: 99%
“…Being able to capture standards-based user feedback enables database-driven algorithm development and enhancement, as well as easy and structured data capture. This is illustrated with a locally developed algorithm for leadless implanted electronic device algorithm for determination of MRI safety based on Chest X-Rays [7]. This algorithm is trained to recognize potentially MRI-unsafe devices using two cascading AI models (the results of the first model for detection based on a fast R-CNN then feed into the second model for identification based on a multi-class CNN).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations